Enforcement Of Environmental And Forestry Laws Against Tapping Of Pine Sap In Samosir Regency, North Sumatra - Simalangon, Roiman; sulistyawaty, Sri; Pakpahan, kartina (Jurnal Ilmu Hukum Reusam, 2024)
Pine tree sap is one of the benefits of forest products managed by farmer groups and the general public. The utilization of pine tree sap or in the Makkoak and Manderes areas, has a very bad impact on the sustainability of pine trees in protected forests or industrial forests in the Samosir district area. This paper explains related to management licensing, pine sap extraction, the impact of pine sap on the community's economy, adverse impacts on forest plantation and several other problems in the utilization of pine sap in Samosir district. In this paper, qualitative/quantitative descriptive analysis is used to analyze primary data obtained through interviews and observations in the field and secondary data through related institutions or agencies. The researcher in this writing found that there were violations of laws, regulations and also violations of agreements and agreements between the farmer group and KPH III Dolok Sanggul in the utilization of pine tree sap. As a result, pine tree plantations that are not good will have a very bad impact on protected forests and industrial forests.